Meteorological forecasts and the pricing of weather derivatives - Matthias Ritter; Oliver Mußhoff; Martin Odening (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
In usual pricing approaches for weather derivatives, forward-looking information such as meteorological weather forecasts is not considered. Thus, important knowledge used by market participants is ignored in theory. By extending a standard model for the daily temperature, this paper allows the incorporation of meteorological forecasts in the framework of weather derivative pricing and is able to estimate the information gain compared to a benchmark model without meteorological forecasts. This approach is applied for temperature futures referring to New York, Minneapolis and Cincinnati with forecast data 13 days in advance. Despite this relatively short forecast horizon, the models using meteorological forecasts outperform the classical approach and more accurately forecast the market prices of the temperature futures traded at the Chicago Mercantile Exchange (CME). Moreover, a concentration on the last two months or on days with actual trading improves the results.
Keywords: C53; G13; G17; N23; 330; weather forecasting; weather risk; price forecasting; financial markets; temperature futures; CME; Wetter; Prognoseverfahren; Finanzderivat; Elementarschadenversicherung; Optionspreistheorie; Theorie; USA